Fenomena Lupa dalam Hafalan Kitab Santriwati (Berdasarkan Tinjauan Teori Decay dan Teori Interferensi) - Saputri, Septia Nur; Tarsono, Tarsono; Hasbiyallah, Hasbiyallah (Faculty of Ushuluddin and Humanities, 2023)
Forgetting is one of the problems or learning difficulties faced by students, so it must be overcome. Namely, by identifying the factors that cause forgetting early, it could devise solutions to overcome them. In this regard, this study aims to describe the phenomenon of forgetting in the memorization of female students' books at the Thohir Yasin Modern Salaf Islamic Boarding School based on a review of Decay theory and Interference theory, the phenomenon of forgetting in question is the factors that cause forgetting and efforts to overcome it. Researchers used qualitative research methods with a descriptive approach to describe the phenomenon of forgetting. The study results show that two things cause the phenomenon of forgetting among female students. First, forgetting is due to long and not repeated memorization; this follows Decay's theory. Second, forget because there is new memorization every day. This research can be a reflection for teachers and students to overcome the problem of forgetting their memory or memorizing a learning material. Keywords: Decay theory and Interferensi theory, Forgetting, Phenomenon